Automatically adaptive cooling of hotspots by a fractal microchannel heat sink embedded with thermo‐responsive hydrogels. (14th October 2021) - Yan, Yunfei; He, Ziqiang; Wu, Gange; Xu, Fulei; Li, Lixian; Zhang, Li
Summary: A smart fractal microchannel heat sink (SFMHS) integrated with thermo‐responsive hydrogels is developed for the randomly distributed hotspots sensing and adaptive cooling of microelectronic devices. The equally distributed thermo‐responsive hydrogels can firstly sense the temperature rise caused by random hotspots and then work as microfluidic valves to reallocate the coolant by its adaptive thermo‐shrinkage. The CFD numerical results show that the proposed SFMHS presents lower and more uniform temperature distribution than FMHS under hotspots conditions. The maximum temperature rise, heat source temperature difference, and heat source temperature SD of SFMHS are 4.47, 4.28, and 0.97 K lower than FMHS at the HSB heat flux of 400 W/cm 2, respectively. The adaptive cooling superiority of SFMHS gets enhanced with the increase of the hotspots area and heat flux density because more hydrogels shrink, and more flow gets reallocated for hotspot‐targeted cooling. However, too low (HSA, 400 W/cm 2 ) or too high (HSC, 300 W/cm 2 ) hotspots conditions would result in the worse hotspot cooling of SFMHS with no adaptive flow reallocation because all hydrogels are at the same initial or shrunken sates. Meanwhile, SFMHS is more effective to sense and cooling the hotspots that are closer to hydrogels.